IDENTIFIKASI PENGGUNAAN MEDIA PEMBELAJARAN DALAM MENGEMBANGKAN KEMAMPUAN BAHASA ANAK USIA 4-5 TAHUN - Hardianti, Farlina (LPPM Institut Pendidikan Nusantara Global, 2021)
This study aims to: 1. Identify what learning media are used in developing the language of children aged 4-5 years, 2. To identify what learning media are dominantly used in developing the language of children aged 4-5 years, 3. To identify media What kinds of learning are effectively used in developing the language of children aged 4-5 years. The type of research used was survey research. Methods and data collection in the study were observation, interviews, and documentation. The sample in this study was 20% of the 26 PAUD in Sekarbela District, so that the research sample was obtained as many as 5 PAUD in Sekarbela District. The results of the research and data analysis showed that the learning media used in developing the language of children aged 4-5 years in PAUD Sekarbela District were 29 learning media or as many as 82.9% of 35 learning media which were included in 4 indicator items, and learning media which are dominantly used in developing the language of children aged 4-5 years in PAUD Sekarbela as many as 5 learning media or as much as 14.2% of 35 learning media which are included in 3 indicator items, as well as effective learning media used in developing children's language. 4-5 years in PAUD Sekarbela District as many as 4 learning media or 11.4% of the 35 learning media which are included in 2 indicator items.